Biomedical Applications of Metals (Springer International Publishing, 2018)
Focused more specifically on the recent advances in applications of various metals and their complexes used in biomedicine, particularly in the diagnosis and treatment of chronic diseases. The editors give equal importance to other key aspects such as toxicological issues and safety concerns. The application of metals in the biomedical field is highly interdisciplinary and has a broad appeal across all biomedical specialties. Biomedical Applications of Metals is particularly focused on covering the role of metals in medicine and the development of novel therapeutic products and solutions in the form of alternative medicines, and some topics on Indian traditional medicine i.e., "Ayurveda". In Section I, the book discusses the role of metals in medicines and include chapters on nanoparticles, noble metals, medical devices, copper. selenium, silver, and microbial pathogens; while Section II includes topics on metals toxicity including heavy metals, carcinogens, cancer therapy, Bhasma's and chelating agents used in Ayurveda, and biochemical and molecular targets including actions of metals. These new and emerging concepts of applications of metals in medicine, their crucial role in management of microbial resistance, and their use in the treatment of various chronic diseases is essential information for toxicologists, and clinical and biomedical researchers.